An Overview of the Safety, Efficiency, and Signal Pathways of Stem Cell Therapy for Systemic Lupus Erythematosus - Qian Yang; Yiping Liu; Guangyong Chen; Wancong Zhang; Shijie Tang; Tianbiao Zhou (Hindawi Limited, 2021)
Systemic lupus erythematosus (SLE) is an autoimmune disease that affects multiple organs and tissues. Mesenchymal stem cells (MSCs) are considered a good source for autoimmune disease and hematological disease therapy. This review will summarize the efficacy, safety, and mechanisms of MSC therapy for SLE. MSC therapy can reduce anti-dsDNA, antinuclear antigen (ANA), proteinuria, and serum creatinine in SLE patients. In animal models of SLE, MSC therapy also indicates that it could reduce anti-dsDNA, ANA, proteinuria, and serum creatinine and ameliorate renal pathology. There are no serious adverse events, treatment-related mortality, or tumor-related events in SLE patients after stem cell treatment. MSCs can inhibit inflammatory factors, such as MCP-1 and HMGB-1, and inhibit inflammation-related signaling pathways, such as the NF-κB, JAK/STAT, and Akt/GSK3β signaling pathways, to alleviate the lesions in SLE.